Seroprevalence of HIV in ANC clinic attendees and utilization of PPTCT services at a tertiary care hospital of western Rajasthan, India - Mehta, Swati; Bhati, Balgopal Singh; Mehta, Lokesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Human immunodeficiency virus (HIV) infection in pregnant women has an important role in its spread to paediatric population by means of vertical transmission. Effective utilization of PPTCT services can reduce this spread. This study aims to determine seroprevalence of HIV in antenatal women, demographic factors of seropositive women and utilization of PPTCT services to minimize the risk of mother to child transmission. Methods: A retrospective study was done among pregnant women attending antenatal clinic of a tertiary care hospital within a period of two years from November 2013 to October 2015. Pre-test counselling, HIV testing, and post-test counselling were done as per NACO guidelines. Antiretroviral prophylaxis was given to seropositive women and their children. Analysis of demographic data of seropositive women and assessment of utilization of PPTCT services was done. Results: Out of 40,913 new antenatal registrations 26,803 (65.58%) women attended pre test counselling and 24716(60.41%) of them accepted HIV testing. Thirty-eight women were found to be seropositive with a seroprevalence rate of 0.16%. Majority of seropositve women were young primigravida, illiterate housewives belonging to rural area. Eight out of 33 partners of seropositive women tested, were found to be seronegative. Out of the 38 seropositive women, 4(10.52%) opted for pregnancy termination, and 31(81.57%) had delivery in our institution. All mother and baby pairs received antiretroviral prophylaxis. Conclusions: Seroprevalence of HIV infection in antenatal women is relatively low in this region than the national average and acceptance of therapeutic interventions to reduce the mother to child transmission is high. There is scope to improve acceptance of counselling and testing of HIV.